Prediksi Erosi dan Perencanaan Konservasi Tanah dan Air pada Daerah Aliran Sungai Yeh Ho di Kabupaten Tabanan - PRASAD, I GUSTI NGURAH GAURA GOPAL PRASAD; TRIGUNASIH, NI MADE; SUMARNIASIH, MADE SRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.2, April 2021, 2021)
Erosion Prediction and Planning of Soil Water Conservation at Yeh Ho Watershed in Tabanan Regency The actual problem in the Yeh Ho watershed is the use of land with steep slopes to steep slopes for the use of mixed gardens without conservation measures and poor land cover conditions. The objectives of this study are to predict the magnitude of actual erosion that occurs (A) in the Yeh Ho watershed and to plan soil and water conservation techniques on land units whose erosion exceeds the allowed erosion (Edp) in the Yeh Ho watershed in Tabanan Regency. The method used in this study is a survey/observation method that is taking data in the field and continued with soil analysis in the Soil Laboratory of the Faculty of Agriculture, Udayana University. The stages of the research were carried out in five stages of work, namely: (1) Determination of land units, (2) Field observations and soil sampling, (3) Laboratory analysis and data processing, (4) Erosion prediction using USLE (Universal Soil Loss Equation) method, (5) Determination of allowable erosion and soil and water conservation planning if the actual erosion exceeds the allowable erosion. The results showed that erosion that occurred in the Yeh Ho watershed was classified as very mild to mild at 0.06 to 34.89 tons/ha/yr. Very light erosion occurred inland units 1, 2, 5, 6, 7, 8, 10, and 13 with an area of ??11,096 ha with erosion that occurred in the range of 0.06 to 3,226 tons/ha/yr, mild erosion occurred inland units 3, 4,9,11, and 12 with an area of ??4,868 ha with erosion that occurred from 4.93 to 52.57 tons/ha/year. The land that requires conservation measures covers 1,717 ha from the area of ??the study area and the land that needs to be maintained is 11,096 ha. It is expected that the people in the Yeh Ho watershed in Tabanan Regency can pay attention to land management by maintaining and conserving so that the actual erosion that occurs does not exceed the allowable erosion.